Brain Ischemia as a Prelude to Alzheimer's Disease - Pluta, Ryszard; Januszewski, Sławomir; Czuczwar, Stanisław J. (Frontiers in Aging Neuroscience, 2021)
Transient ischemic brain injury in animals and humans generated a massive neuronal death in the hippocampus. This was accompanied by progressive atrophy of the hippocampus, brain cortex and white matter lesions. Furthermore, it was noted that neurodegenerative processes after ischemia-reperfusion brain episode continued well beyond the acute stage. Rarefaction of white matter was significantly increased in animals during 2 years following ischemia. Some rats that survived 2 years after ischemia developed severe brain atrophy with dementia. The profile of post-ischemic brain neurodegeneration shares a commonality with neurodegeneration in Alzheimer’s disease. What is even more, post-ischemic brain injury is associated with the deposition of folding proteins, such as amyloid and tau protein, in the intra- and extracellular space. Recent information in understanding post-ischemic brain neurodegeneration have revealed dysregulation of Alzheimer’s disease associated genes such as: amyloid protein precursor, α-secretase, β-secretase, presenilin 1 and presenilin 2, and tau protein. The latest data demonstrates that Alzheimer’s disease-related proteins and their genes play a key role in the development of post-ischemic brain neurodegeneration with full-blown dementia of Alzheimer’s disease type. Ongoing interest in brain ischemia study has provided evidence showing that ischemia may be involved in the development of Alzheimer’s disease genotype and phenotype, suggesting that brain ischemia can be considered as a useful model for understanding mechanisms responsible for the initiation Alzheimer’s disease.